Altered Effective Connectivity in Schizophrenic Patients With Auditory Verbal Hallucinations: A Resting-State fMRI Study With Granger Causality Analysis - Gao, Jie; Zhang, Dongsheng; Wang, Lei; Wang, Wei; Fan, Yajuan; Tang, Min; Zhang, Xin; Lei, Xiaoyan; Wang, Yarong; Yang, Jian; Zhang, Xiaoling (Frontiers in Psychiatry, 2020)
Purpose: Auditory verbal hallucinations (AVH) is most common and prominent symptom of schizophrenia. Although abnormities of functional connectivity associated with AVH have been reported in multiple regions, little knowledge is known with regard to information flow as yet. This study aims to investigate the causal influences among key regions in auditory, language and memory networks related to AVH based on granger causality analysis(GCA). Patients and methods: 18 schizophrenia with AVH and 18 matched patients without AVH who accepted resting-state fMRI scans were enrolled. Bilateral superior temporal gyrus(STG), Broca’s area, Wernicke’s area, putamen and hippocampus were selected as regions of interest. Results: The results of GCA showed increased granger causality(GC) from Broca’s area to left STG and decreased GC from right homologue of Wernicke’s area to right homologue of Broca’s area, from right STG to right hippocampus in AVH group compared with the non-AVH group. Meanwhile, correlation analysis exhibited that the normalized ratios of GC from the left STG to the Broca’s area, from the left STG to the right homologue of Broca’s area, from the right STG to the right homologue of Broca’s area were negatively correlated with the severity of AVH, and the normalized ratios of GC from the Broca’s area to the left hippocampus, from the Broca’s area to the right STG were positively correlated with the severity of AVH. Conclusion: These findings characterize the causal influence among pivotal regions involving the auditory, the language and memory networks in schizophrenia with AVH, which provided a deep understanding of neural mechanisms underlying AVH.